IMPLEMENTASI TEKNOLOGI CEN-DSRC PADA ELECTRONIC ROAD PRICING (ERP) SEBAGAI SOLUSI MENGATASI MONOPOLI SISTEM DAN KEMACETAN DI JALAN TOL - Hasad, Andi (RESULTAN : Jurnal Kajian Teknologi, 2010)
Road Fund DSRC technology is non-standard technology like in Japan and the United States that allow the monopoly system of the absence of competitors in its implementation. While the technology CEN-DSRC standards, quite a lot of competitors such as Q-Free, Kapsch, CS Route, Efkon, Thales and Telvent, so the monopoly of one operator can be avoided. Road Fund in Indonesia can be done by applying the Electronic Road Pricing (ERP) application, where one of the Electronic Toll Collection (ETC). To avoid monopoly and the ETC ERP implementation in Indonesia should use the reference standard. Latest technologies that are standard in the world today are technology CEN - DSRC, which has a high level of interoperability so that eventually every region in Indonesia may be different from different vendors or service in the implementation in the field, eg on the highway. By using the CEN standards - DSRC, indonesia later public transport, just use one standard for RFID technology in motor vehicles of On Board Units (OBU) which can be used for all toll road operators, in every regional autonomy for ERP, ETC as well as to pay off Road Parking, Security, etc. systems